Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To evaluate the indefinite integral [tex]\(\int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx\)[/tex], let's break down the integral into two parts and solve each part separately.
The integral can be written as:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = \int \frac{5}{\sqrt{x}} \, dx + \int 5 \sqrt{x} \, dx \][/tex]
### Evaluate [tex]\(\int \frac{5}{\sqrt{x}} \, dx\)[/tex]
First, let's simplify [tex]\(\frac{5}{\sqrt{x}}\)[/tex]:
[tex]\[ \frac{5}{\sqrt{x}} = 5 x^{-\frac{1}{2}} \][/tex]
Now we can integrate [tex]\(5 x^{-\frac{1}{2}}\)[/tex]:
[tex]\[ \int 5 x^{-\frac{1}{2}} \, dx \][/tex]
Use the power rule of integration, which states [tex]\(\int x^n \, dx = \frac{x^{n+1}}{n+1} + C\)[/tex] for [tex]\(n \neq -1\)[/tex]:
[tex]\[ n = -\frac{1}{2} \][/tex]
[tex]\[ \int x^{-\frac{1}{2}} \, dx = \frac{x^{-\frac{1}{2} + 1}}{-\frac{1}{2} + 1} = \frac{x^{\frac{1}{2}}}{\frac{1}{2}} \][/tex]
Multiply by the constant 5:
[tex]\[ \int 5 x^{-\frac{1}{2}} \, dx = 5 \cdot 2 x^{\frac{1}{2}} = 10 \sqrt{x} \][/tex]
### Evaluate [tex]\(\int 5 \sqrt{x} \, dx\)[/tex]
First, let's rewrite [tex]\(\sqrt{x}\)[/tex] using exponents:
[tex]\[ \sqrt{x} = x^{\frac{1}{2}} \][/tex]
Now we can integrate [tex]\(5 x^{\frac{1}{2}}\)[/tex]:
[tex]\[ \int 5 x^{\frac{1}{2}} \, dx \][/tex]
Use the power rule of integration:
[tex]\[ n = \frac{1}{2} \][/tex]
[tex]\[ \int x^{\frac{1}{2}} \, dx = \frac{x^{\frac{1}{2} + 1}}{\frac{1}{2} + 1} = \frac{x^{\frac{3}{2}}}{\frac{3}{2}} \][/tex]
Multiply by the constant 5:
[tex]\[ \int 5 x^{\frac{1}{2}} \, dx = 5 \cdot \frac{2}{3} x^{\frac{3}{2}} = \frac{10}{3} x^{\frac{3}{2}} \][/tex]
### Combine the results
Adding the results of both integrals:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = 10 \sqrt{x} + \frac{10}{3} x^{\frac{3}{2}} + C \][/tex]
To present the final answer neatly:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = \frac{10}{3} x^{\frac{3}{2}} + 10 \sqrt{x} + C \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
The integral can be written as:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = \int \frac{5}{\sqrt{x}} \, dx + \int 5 \sqrt{x} \, dx \][/tex]
### Evaluate [tex]\(\int \frac{5}{\sqrt{x}} \, dx\)[/tex]
First, let's simplify [tex]\(\frac{5}{\sqrt{x}}\)[/tex]:
[tex]\[ \frac{5}{\sqrt{x}} = 5 x^{-\frac{1}{2}} \][/tex]
Now we can integrate [tex]\(5 x^{-\frac{1}{2}}\)[/tex]:
[tex]\[ \int 5 x^{-\frac{1}{2}} \, dx \][/tex]
Use the power rule of integration, which states [tex]\(\int x^n \, dx = \frac{x^{n+1}}{n+1} + C\)[/tex] for [tex]\(n \neq -1\)[/tex]:
[tex]\[ n = -\frac{1}{2} \][/tex]
[tex]\[ \int x^{-\frac{1}{2}} \, dx = \frac{x^{-\frac{1}{2} + 1}}{-\frac{1}{2} + 1} = \frac{x^{\frac{1}{2}}}{\frac{1}{2}} \][/tex]
Multiply by the constant 5:
[tex]\[ \int 5 x^{-\frac{1}{2}} \, dx = 5 \cdot 2 x^{\frac{1}{2}} = 10 \sqrt{x} \][/tex]
### Evaluate [tex]\(\int 5 \sqrt{x} \, dx\)[/tex]
First, let's rewrite [tex]\(\sqrt{x}\)[/tex] using exponents:
[tex]\[ \sqrt{x} = x^{\frac{1}{2}} \][/tex]
Now we can integrate [tex]\(5 x^{\frac{1}{2}}\)[/tex]:
[tex]\[ \int 5 x^{\frac{1}{2}} \, dx \][/tex]
Use the power rule of integration:
[tex]\[ n = \frac{1}{2} \][/tex]
[tex]\[ \int x^{\frac{1}{2}} \, dx = \frac{x^{\frac{1}{2} + 1}}{\frac{1}{2} + 1} = \frac{x^{\frac{3}{2}}}{\frac{3}{2}} \][/tex]
Multiply by the constant 5:
[tex]\[ \int 5 x^{\frac{1}{2}} \, dx = 5 \cdot \frac{2}{3} x^{\frac{3}{2}} = \frac{10}{3} x^{\frac{3}{2}} \][/tex]
### Combine the results
Adding the results of both integrals:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = 10 \sqrt{x} + \frac{10}{3} x^{\frac{3}{2}} + C \][/tex]
To present the final answer neatly:
[tex]\[ \int \left( \frac{5}{\sqrt{x}} + 5 \sqrt{x} \right) \, dx = \frac{10}{3} x^{\frac{3}{2}} + 10 \sqrt{x} + C \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.